The effect of alterations in foot centre of pressure on lower body kinematics during the five-iron golf swing - Faux, L.; Carlisle, A.; Vickers, J.; Diss, C. (Journal of Sports Sciences, 2019)
The research aimed to evaluate the effects of an intervention aimed at altering pressure towards the medial aspect of the foot relating to stability mechanisms associated with the golf swing. We hypothesised that by altering the position of the foot pressure, the lower body stabilisation would improve which in turn would enhance weight distribution and underpinning lower body joint kinematics. Eight professional golf association (PGA) golf coaches performed five golf swings, recorded using a nine-camera motion analysis system synchronised with two force platforms. Following verbal intervention, they performed further five swings. One participant returned following a one-year intervention programme and performed five additional golf swings to provide a longitudinal case study analysis. Golf performance was unchanged evidenced by the velocity and angle of the club at ball impact (BI), although the one-year intervention significantly changed the percentage of weight experienced at each foot in the final 9% of downswing, which provided an even weight distribution at BI. This is a highly relevant finding as it indicates that the foot centre of pressure was central to the base of support and in-line with the centre of mass (CoM), indicating significantly increased stability when the CoM is near maximal acceleration.